An in-Depth Examination Modalities of Hemodynamic Characteristics in Mechanical Aortic Valve: A Comprehensive Review Article - Tariq, Qabas; Jaber, Samar Ali; Ammar, Ahmed (Al-Nahrain Journal for Engineering Sciences, 2023)
The assessment of prosthetic aortic valves through echocardiography, a pivotal noninvasive tool, encounters challenges, with discordant findings compared to invasive measurements, particularly in transvalvular gradients. To address these complexities, this comprehensive review article explores diverse methodologies and modalities for assessing prosthetic aortic valve performance. As these life-saving devices advance in complexity, the demand for precise and innovative assessment techniques intensifies. This journey through established and emerging modalities aims to inform clinical practice, foster experimental innovation, and enhance patient care in the realm of aortic valve prosthetic assessment. Ultimately, a profound understanding of the hemodynamic milieu engendered by aortic prosthetic valves serves as the cornerstone for optimizing valve design and clinical utility. The primary objective of this comprehensive review is to elucidate, with utmost precision, the multifaceted methodologies employed in the investigation and evaluation of mechanical prosthetic aortic valve.